Plant Location with Generalized Search Origin - Spielberg, Kurt (Management Science, 1969)
There exists computational experience to the effect that search algorithms of the type introduced by Balas are frequently ineffective because of being tied to a rigid “natural” search origin. In this paper the dynamic relocation of the search origin to possibly more appropriate points is advocated. Details of such a procedure are given for the Simple Plant Location Problem. Computational improvements of, sometimes, a striking nature are presented.